An enlightenment Tory in Victorian Scotland : the career of Sir Archibald Alison - Michie, Michael (McGill-Queen's studies in the history of ideas, 1997)
"An Enlightenment Tory in Victorian Scotland is a political and intellectual biography of Sir Archibald Alison (1792-1867), historian, social critic, criminal lawyer, and sheriff of Lanarkshire. The first author to examine the full range of Alison's writings and activities, Michael Michie reveals a significant link between the Scottish Enlightenment and Victorian conservatism."--Jacket